Language universals and their characteristic features (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
Language universals refer to the features that are shared by all natural human languages. Linguists have long been interested in uncovering these universals to better understand the fundamental characteristics of human language. A few characteristic features of language universals include:• Phonological Universals: These universals pertain to the basic sound structure of language. For instance, nearly all languages have consonants and vowels, and they organize these sounds into patterns that allow for meaningful communication.• Grammatical Universals: This category encompasses the common structural features found in the grammars of all languages. For instance, the presence of nouns and verbs in the vast majority of languages, as well as the use of word order or inflection to denote grammatical relationships.• Semantic Universals: These universals relate to the ways in which languages express meaning. For example, most languages make distinctions between past, present, and future tenses, and also have words to express basic emotions like happiness and sadness.• Pragmatic Universals: Pragmatics deals with the use of language in context. Universals in this domain include the ability to ask questions, make requests, and use politeness markers, which are present in some form across most languages.• Genetic Universals: These universals refer to the biological constraints on the human capacity for language. For example, all humans are born with the ability to acquire language, and this ability emerges during early childhood.